“It’s Good to Have a Voice”: What Do Students Think about the Impact of a Flexible Curricular Implementation of Student-Centered Pedagogies on Their Own Learning Experiences? - Rita Silva; Cláudio Farias; Isabel Mesquita (Education Sciences)
While there is extensive evidence that student-centered pedagogies (SCPs) develop multidimensional (motor, cognitive, social) outcomes in students, the coalesced use of some of the core pedagogies of student-centered models (SCMs) can facilitate the achievement of more than one educational theme in the same intervention and may facilitate student engagement in more representative physical education (PE) experiences. In this study, students’ voices are explored concerning the impact of a flexible and coalesced curricular implementation of SCPs on their own PE learning experiences. An insider action-research design was implemented for one entire school year (50 lessons of 90 min each) with 25 students aged 16–17 years, enrolled in the 12th grade at a high school in Portugal. A qualitative data collection source was used (semi-structured focus-group interviews), analyzed through a mixed inductive–deductive thematic analysis. The findings emphasize that a flexible and coalesced curricular implementation of various SCPs over an extended period of time, considering the sport content, the context, and the skill level of students, seems to contribute to the development of more positive learning experiences for students. In summary, these learning experiences require that teachers learn to listen and respond to students’ voices.